Platsens sanning. Performativitet och gränsdragningar i tornedalsk litteraturhistoria och grammatik - Anne Heith (Nordlit: Tidsskrift i litteratur og kultur, 2012)
The language Meänkieli is an official minority language in Sweden since the year 2000. The acknowledgement of the existence of historical linguistic minorities reflects the fact that  Sweden  has  always  been  a multiethnic  and  multilingual  space.  Long  before  the present day borders were established there were Sami people and Finno-Ugric groups of people in the northernmost parts of Scandinavia. Since a couple of decades the cultural mobilization among the Swedish Tornedalians has been intensified. Publishing houses which  publish  in  Meänkieli (previously  called  Tornedalian  Finnish)  have  been established. Furthermore there are conscious attempts at constructing a literary tradition and at producing grammar books of Meänkieli. In 2007 the first volume of a Tornedalian literary history co-authored by Bengt Pohjanen and Kirsti Johansson was published, Den tornedalsfinska  litteraturen. Från  Kexi  till  Liksom.  Two  years  later  a  second  volume, Den tornedalsfinska  litteraturen.  Från  Kalkkimaa  till  Hilja  Byström,  was published. Both volumes performatively construct a specific Tornedalian literary tradition which is distinguished  from  a  Swedish  national tradition.  This  may  be  interpreted  as  a  deconstruction of notions of a homogeneous Swedish nation through the production of local truths which challenge culturally homogenizing nation-building.